Strategi Pemasaran Melalui Pesan Dalam Iklan Rokok Sampoerna Hijau Di Televisi Versi Datang Kondangan - Yehuda Yehuda (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Commercial advertisement aims to convey communication messages that are delivered by the company to potential customers. Advertising is a medium where someone shows something to others, with hope that the other person will do something to fulfill the desire of the message sender. In commercial advertisement, a company does its effort to sale its product by using engaging languages. However, there is a unique thing in the world of cigarette advertising in Indonesia. Government regulations prohibit cigarette manufacturers to promote their products using a direct language in broadcast media. This encourages cigarette manufacturers to do creative things in creating ads. One way is by using pictures, signs, and implied languages. Based on the principles in the theory of speech acts, Austin (1978: 101) distinguished three kinds of speech acts, namely locution, ilocution and perlocution, that occur simultaneously. In this journal, the author will focus on a Cigarette Ad namely Sampoerna Hijau version of "Visiting Invitation", with its tagline "The Pleasure of Togetherness". The analysis on this ad aims to analyze what implied messages actually in this ad, which are more detailed, such as the form of speech acts locution, ilocution and perlocution in advertising. The advertisement "Visiting Invitation" does not seem to have anything to do with Sampoerna Hijau Cigarettes. Thus, it is necessary to do analysis using Semiotics method to find the relationship between the advertisement  and the expectation of producer to make the audience buy his product.